Innovation of Ma'had Saad Bin Abi Waqqash In Moral Development - Adi Bahtiar (Borneo Educational Journal (Borju), 2023)
This study aims to analyze efforts to develop student morals and the supporting and inhibiting factors at Ma'had Saad bin Abi Waqqash Palembang. This research is a field research, the type of data used is qualitative data and the informants in this research are some lecturers and two Ma'had administrators. Methods of data collection using in-depth open interviews, observation, and documentation. The data analysis method used is descriptive qualitative. The results of the research show that the lecturer's efforts in fostering student morals are by the method of giving descriptions to students about the meaning and importance of morals, habituation by strengthening programs, upholding discipline, creating conducive and Islamic nuances of ma'had areas, preparing reference books on lecturer morals and exemplary. In general, student morals can be said to have been good with activities and activities implemented through moral aspects, basic matters regarding good morals, piety to Allah, temperament and character and are active and participate in programs that have been implemented in the ma'had area or in the hostel. The system applied in shaping student morals in an Islamic way is to return to the Al-Qur'an and Sunnah, exemplary, supervision, advice, habituation, guidance, learning and discipline.